Gênese e variabilidade das chuvas na região norte-noroeste do estado de Minas Gerais - Felipe Pereira de Moura (2021)
Environmental studies are undeniably important for the development of societies. Knowledge about the environment allows for better planning of its use and occupation, making it possible to establish potentials and risks related to different areas. Studies in climatology allow for an improvement in knowledge about climate dynamics and the elements that constitute it. The importance of understanding climate dynamics is verified, since its performance directly affects society and, in this sense, climate variability is a fundamental aspect to be considered both for planning human activities and for environmental management. Thus, this research aims to analyze the factors linked to the genesis, distribution and variability of rainfall in the north-northwest region of the state of Minas Gerais in the period from 1961 to 2016 and, from the interaction of this attribute with factors of the physical environment, propose an outline of the compartmentalization (or delimitation) of the rainfall units for the region, as a way of synthesizing the amount of information produced during the development of the research. The data from the historical series were used in the construction of graphs, application of statistical techniques and in the construction of maps. The “Box Plot” technique allowed visualizing trends in precipitation variation and classifying the data on a monthly basis due to the precipitation regime. There was a preponderance of dry and normal months over the others. Regarding the compartmentalization of rainfall units, five were established, two of which were more humid and three were drier. The other areas were considered as transition zones due to their rainfall characteristics.